Beliefs, performance, and applicability of mathematics in learning for life: The multi-case study at secondary education institutes in Italy - Malvasi, Viviana; Gil-Quintana, Javier (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2022)
Our study stars with the aim of discovering if there is a relationship between the beliefs and perceptions that Italian High School students have towards mathematics and some factors as grade, macro area, type of school and academic performance. The methodological proposal that this study follows is based on the combination of quantitative and qualitative method. Regarding the quantitative design, the instrument used has been a survey filled out by 4845 students living in Italy. The qualitative methodology has focused on the discourse analysis of 12 in-depth interviews with the participation of secondary school teachers. Among the main results we found that the perception of mathematics as a useful subject just to count, calculate and measure can be considered among the causes of the decrease academic performance of the students of the Second Grade Secondary School compared to the Primary School, because many students consider utility of math just in its arithmetic aspect. In addition, while changes about beliefs by grade, macro area and type of school are not significant, we found correlations between some particular beliefs and performance in mathematics, confirming a connection between beliefs towards this discipline and academic performance. The novelty of our research is found in having specifically detected which are beliefs and perceptions related to academic performance. That opens the door for future research.